Cooperative methods and self-regulated strategies development for argumentative writing. Issue 1 (2nd January 2019) - Prata, Maria José; de Sousa, Bruno; Festas, Isabel; Oliveira, Albertina L.
ABSTRACT: The authors analyze the efficacy of a cooperative method associated with self-regulated strategy development (SRSD) for argumentative writing compared with a SRSD single approach. Seven teachers and 230 ninth-grade students from three middle schools participated in the present study in which teachers were part of a practice-based professional development program. Schools were assigned either to the experimental group or to the comparison group. Over a three-month period, all students were taught SRSD strategies. After this period, students from the experimental group participated in a cooperative setting, whereas the comparison group followed the SRSD only. The results indicated that students in the experimental group made statistically significant greater gains in structural argumentative elements and in the quality of writing texts immediately after the intervention and one month later. Thus, the study provides evidence for the benefits of adding a cooperative setting to SRSD in implementing argumentative writing skills.